The Effect Of Credit Derivatives On Hedging Risk Of Non-Payment: Applied Research - Iftikhar Jabbar Abed; Safa Mahdi Raji; Sahar Jabbar Rahman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of the current research is to reveal the impact of credit derivatives by (purchased credit derivatives, the value of credit derivatives sold) in hedging the risk of non-payment at a sample of commercial banks in the Iraq Stock Exchange by (Middle East Bank, Gulf Commercial Bank, Trade Bank of Iraq, Bank of Baghdad, Credit Bank) for the financial period from (2016-2020), and for the purpose of analyzing the results, the Office package was adopted (Excel.V.2016) in order to extract the level of credit derivatives, And the risks of non-payment at the commercial banks surveyed, has been using a set of statistical methods to determine these variables, represented in (credit derivatives, arithmetic mean, correlation coefficient, and regression coefficient), as a result, the research came out with a set of results, foremost of which was that there is an effect of credit derivatives in hedging the risks of non-payment, and this shows that credit derivatives contribute to improving the ability to hedge against non-payment risks, allowing investors to reduce financial risks. The focus of the surveyed commercial banks on the use of credit derivatives to protect investors from fluctuations in interest rates and currency rates, which works to reduce the impact of non-payment risks on their profits, which means that these contracts allow the determination of a future price for financial assets.